Mammographic and Ultrasonographic Evaluation of Palpable Abnormalities of the Breast - Pushpkant Tiwari; Suvendu Ghosh; Vijender Kumar Agrawal (Medsci Publications, 2017)
Introduction: The mammography (MG) and ultrasonography (USG) are individually effective diagnostic modalities for palpable abnormalities of the breast. This study was carried out with a aim to evaluate breast lesions using mammography and ultrasonography independently and in combination with FNAC correlation. Methods: This cross-sectional hospital-based study was carried out at department of Radio diagnosis in a tertiary care hospital of West Bengal. Study participants were all women with palpable and non palpable breast lesions detected on clinical examination/self breast examination and referred for mammography and women in high risk groups Results: The sensitivity, specificity, positive predictive value (PPV) & negative predictive value (NPV) of mammography in detecting carcinoma breast were 77.8%, 97.7%, 87.5% and 95.6% respectively. The sensitivity, specificity, PPV& NPV of USG in detecting carcinoma breast were 55.6%, 97.7%, 83.3% and 91.5% respectively. In our study population 83.0% breast lesion were benign and out of them 77.27% were diagnosed by mammography alone and 72.7% were diagnosed by USG alone. When these modalities were combined, 97.7% of the lesions were diagnosed. Conclusion: This study confirms mammography and ultrasonography when combined have significantly higher sensitivity and negative predictive value in detecting the palpable abnormalities of the breast.